KONTRIBUSI IMAM MASJID DALAM MEMBENTUK PENGKADERAN REMAJA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN DI DESA KINAL JAYA KECAMATAN NAPAL PUTIH BENGKULU UTARA - Wulan Utami, Intan; Syahbudin, Rizkan; Nasron (JPT : Jurnal Pendidikan Tematik, 2020)
The background of this research is that based on observations and initial interviews conducted by the author, it is still found that there are teenagers who have not been able to read the Qur'an in accordance with the science of recitation and there is also no coaching to become a mosque imam in the future. The formulation of the problem in this study is what is the contribution of the mosque's imam in improving the ability to read the Qur'an in Kinal Jaya Village, Napal Putih District, North Bengkulu Regency. The purpose of this study is to find out how the contribution of the Imam of the Mosque in forming youth cadres to improve the ability to read the Qur'an. This study uses a qualitative method with a qualitative descriptive approach. The first analysis technique of this research is data collection, in this data collection using the results of observations, interviews, and documentation. the contribution of the Imam of the Mosque in improving the ability to read the Qur'an is by the way the imam of the mosque in Kinal Jaya Village forms youth cadres. From the youth cadre formed by the Imam of the mosque so that the ability to read the Qur'an of the youth is increasing well. So it can be concluded that the cadre formed by the Imam of the Mosque was successful in improving the ability to read the Qur'an of the youth who took part in the cadre in Kinal Jaya Village, Napal Putih District, North Bengkulu Regency.